Meharia Chrétien, 1915 - new genus in Zimbabwean Fauna (Lepidoptera: Cossidae) - R. V. Yakovlev; Th. J. Witt (SHILAP)
The article gives a new indication on the species of the genus rare for the territory of Africa, Meharia Chrétien, 1915. Meharia ganslmeieri Yakovlev & Witt, 2015 is indicated for the first time for the fauna of Zimbabwe, which significantly extends the habitat of the genus to the South.